Effect of Bidens tripartita leaf supplementation on the organism of rats fed a hypercaloric diet high in fat and fructose - M. A. Lieshchova; V. V. Brygadyrenko (Regulatory Mechanisms in Biosystems, 2024)
Herbs play an important role in folk medicine, and scientific research has confirmed the properties of their use as an alternative treatment, including the treatment and mild correction of metabolic disorders during disease. Trifid bur-marigold (Bidens tripartita) is a pharmacopoeial herbal raw material that is widely used in clinical practice as an external remedy for skin lesions and as an internal remedy for digestive and respiratory disorders. In this work, the general effect of dried leaves of B. tripartita on physiological activity and metabolic processes in model animals on a high-calorie diet was determined. For the experiment, three groups of 18 male white laboratory rats were formed and fed a hypercaloric diet (increased fat content and 20% fructose solution instead of water) for 27 days, in addition to 0.4% and 4.0% dried leaves of B. tripartita. The consumption of 0.4% and 4.0% of the medicinal plant resulted in a significant delay in the body weight gain and the average daily weight gain of the rats compared to the control group. Dried leaves of B. tripartita in the diet of rats decreased the relative weight of the thymus and increased the relative weight of the brain, and at a dose of 4.0%, increased the relative weight of the lungs and individual large intestines (cecum and colon). Dietary supplementation with B. tripartita caused an increase in globulin concentration and changes in protein coefﬁcient. Blood parameters such as: urea, urea nitrogen, inorganic phosphorus, glucose and bilirubin levels changed depending on the dose. In the general blood test, consumption of dried leaves of B. tripartita caused a decrease in hematocrit, hemoglobin concentration and platelet count, but increased the number of eosinophils. Bidens tripartita at both concentrations significantly increased ALT activity with a corresponding change in the blood De Ritis ratio. The addition of 20 g of B. tripartita leaves to the diet increased alkaline phosphatase activity and decreased alpha-amylase activity, while 200 g increased blood gamma-glutamyltransferase activity. At the end of the experiment, the rats' orientation activity, determined in the open field, changed according to the herb dose consumed: 0.4% leaves caused an increase and 4.0% a decrease. Physical activity was reduced and emotional state increased, regardless of the dose of dried B. tripartita leaves, compared to the control group of animals. The results obtained show that the addition of B. tripartita dried leaves as a dietary supplement to a high-calorie diet is safe, does not cause pathological changes or side effects, and has a significant effect on metabolic processes. This provides theoretical support for the use of B. tripartita dried leaves in the manufacture of nutraceutical and pharmacological products for the correction of metabolic disorders in humans and animals. The doses and duration of their application require further studies.